One Minute of Marijuana Secondhand Smoke Exposure Substantially Impairs Vascular Endothelial Function - Xiaoyin Wang; Ronak Derakhshandeh; Jiangtao Liu; Shilpa Narayan; Pooneh Nabavizadeh; Stephenie Le; Olivia M. Danforth; Kranthi Pinnamaneni; Hilda J. Rodriguez; Emmy Luu; Richard E. Sievers; Suzaynn F. Schick; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundDespite public awareness that tobacco secondhand smoke (SHS) is harmful, many people still assume that marijuana SHS is benign. Debates about whether smoke‐free laws should include marijuana are becoming increasingly widespread as marijuana is legalized and the cannabis industry grows. Lack of evidence for marijuana SHS causing acute cardiovascular harm is frequently mistaken for evidence that it is harmless, despite chemical and physical similarity between marijuana and tobacco smoke. We investigated whether brief exposure to marijuana SHS causes acute vascular endothelial dysfunction. Methods and ResultsWe measured endothelial function as femoral artery flow‐mediated dilation (FMD) in rats before and after exposure to marijuana SHS at levels similar to real‐world tobacco SHS conditions. One minute of exposure to marijuana SHS impaired FMD to a comparable extent as impairment from equal concentrations of tobacco SHS, but recovery was considerably slower for marijuana. Exposure to marijuana SHS directly caused cannabinoid‐independent vasodilation that subsided within 25 minutes, whereas FMD remained impaired for at least 90 minutes. Impairment occurred even when marijuana lacked cannabinoids and rolling paper was omitted. Endothelium‐independent vasodilation by nitroglycerin administration was not impaired. FMD was not impaired by exposure to chamber air. ConclusionsOne minute of exposure to marijuana SHS substantially impairs endothelial function in rats for at least 90 minutes, considerably longer than comparable impairment by tobacco SHS. Impairment of FMD does not require cannabinoids, nicotine, or rolling paper smoke. Our findings in rats suggest that SHS can exert similar adverse cardiovascular effects regardless of whether it is from tobacco or marijuana.